River and water bodies: the creator's gift - Zen, Ismawi (Federal Department of Town & Country Planning, Peninsular Malaysia, 2011)
All civilizations were related to mighty rivers: Euphrates, Nile, Indus, Oxus and the Hwang Ho. The earliest conception of paradise has the image of a river deeply embedded within it. This paper outlines the role played by river in the images of paradise as explained in the Quran and the traditions of the Prophet p.b.u.h. It also presented the examples of how this image has inspired the development of Islamic Gardens, whose prototype was innovated and refreshed throughout the Islamic World from Andalusia (Spain) to Persia and Mughul India where it reached its climax.